Od izročil do nesnovne kulturne dediščine - Muršič, Rajko (Etnolog. Nova vrsta (Ljubljana), 2018)
Cultural heritage is originally administrative and bureaucratic concept. Only in last three decades it entered professional use. Ethnomusicologists and folklorists significantly contributed to the formulation of the Unesco's Convention for the Safeguarding of the intangible cultural heritage. However, in Slovenia entries in the national register on music and singing are scarce. Crucial for cultural heritage is its relationship with the government and communities. This is what professional activities should take into account. In Slovenian legislation there is no more mentioning of ethnological cultural heritage, although it should be the first to integrate so far separated domains if its safeguarding.
Keywords: birokracija; bureaucracy; cultural heritage; država; folk music; glasba; intangible cultural heritage; kulturna dediščina; ljudska glasba; music; nesnovna kulturna dediščina; state; traditional music; Unesco